An AIDS-defining neoplasm in a 30-year-old man on highly active antiretroviral therapy: a forgotten diagnosis?. (26th March 2014) - Russell, Mark D; Singh-Ranger, Deepak; Crosbie, James
Abstract : Highly active antiretroviral therapy (HAART) has dramatically improved the morbidity and mortality of patients with HIV. Although the incidence of AIDS-defining neoplasms is decreasing with this therapy, they must still be considered in patients who present with suspicious symptoms. Early diagnosis and treatment may help to improve quality of life and clinical outcome. We report the case of a 30-year-old man on HAART who presented with an expanding lump in the left groin, thought to be a haematoma for 5 months. A high level of suspicion led to a prompt diagnosis of Burkitt's lymphoma followed by timely treatment with chemotherapy. This culminated in complete remission, with an improved quality of life.